Better wed over the mixen than over the moor? Break-ups of inter-ethnic marriages in Italy - Laura Bottazzi; Paolo Manasse; Sarah Grace See (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2017)
This paper studies the resilience of inter-ethnic marriages in Italy through the lenses of marriage duration by means of survival and treatment-effect analyses. Our main findings are that inter-ethnic marriages have a significantly higher risk of separation even when we control for social and economic characteristics of the spouses; however, when we restrict the analysis to more recent marriages, we observe that co- and inter-ethnic marriages converge in longevity. Finally, we find evidence of self-selection into inter-ethnic marriages. Overall our findings points to a society that is becoming increasingly open to cultural and ethnic diversity, as well as more secular.
Keywords: J12; 330; inter-ethnic marriage; divorce; separation; family economics